Dynamical entanglement of stretching–stretching and stretching–bending vibrations in SO2. Issue 19 (17th December 2014) - Zhai, Liangjun; Zheng, Yujun; Reiher, Markus
<x xml:space="preserve">Abstract</x> The dynamics of stretching–stretching (SS) and stretching–bending (SB) entanglement in the normal mode molecule SO2 are studied by the Lie algebraic method. The influence of the decoherence from the remaining vibrational mode is considered. We have found that SS vibrations can achieve a higher degree of entanglement than the SB vibrations, and the degeneration rate of SB entanglement is higher than the SS entanglement. By the comparative study, the SS vibrations are found to be more suitable to construct a biqubit system rather than the stretching–bending vibrations. © 2014 Wiley Periodicals, Inc.